A New Species of the Bromeligenous Genus Crossodactylodes (Anura: Leptodactylidae: Paratelmatobiinae) from Southeastern Brazil - Ferreira, Rodrigo B.; Zocca, Cássio; Carvalho, Suzana Ellen C.; Haddad, Célio F.B. [UNESP]; Santos, Marcus Thadeu T. [UNESP] (Society for the Study of Amphibians and Reptiles, 2023)
Crossodactylodes is a leptodactylid genus of bromeligenous frogs, currently comprising six species distributed in southeastern and northeastern Brazil. The number of species in the genus is underestimated, as suggested by a recent study that identified at least three putative new species. Here we describe one of these species from the montane Atlantic Forest of southeastern Brazil in the state of Espírito Santo. The new species is distinguished from its congeners by a combination of characters, including the presence of a dorsolateral fold and vomerine teeth, the absence of vocal slits in adult males, and discs of fingers II–IV slightly expanded. We also provide information on its natural history and conservation status. So far, the new species is known only from a forest remnant surrounding an inselberg (rocky outcrop) on private properties. This fact highlights the importance of engaging the local human community in educational outreach activities to protect the new species as well as the ecosystem services provided by the type locality.